Comparison of Three Different Methods of Dressing for Skin Graft Donor Site - Mehdinavaz Aghdam, Abdolreza; Alizadeh, Afshin; Mousavi Toomatari, Seyed Babak; Mousavi Toomatari, Seyed Ehsan (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Background: There are various methods to dress the Skin Graft Donor Site (SGDS), but some are very expensive and not available in Iran. This study aimed to compare three different dressings for the management of the SGDS. Methods: Ninety-six patients participated in the study, and they were randomly divided into three groups. Donor sites were dressed with one of these methods: Vaseline gauze or method A, mupirocin 2% or method B, and nitrofurazone or method C. In each method, the dressing layer was covered by 5 layers of dry gauze. The three groups were compared regarding the epithelialization time, infection, pain, and cost. Results: The epithelialization time was significantly longer in group A compared with groups B and C (P<0.05), but there was no significant difference between groups B and C (P<0.05). There was no significant difference between the three groups in infection and pain at rest, activity, and dressing time (P<0.05). There was a substantial difference between the three groups in the cost of dressing as method A was cheaper. Conclusion: Due to the lower cost of Vaseline gauze and no significant difference in infection, dressing adhesion to the skin, and amount of pain between three dressing methods, Vaseline gauze is a preferred method to skin graft donor site dressing.